Influence of elevated hydrostatic pressure on Müller cells phenotype. Do microglia-derived microvesicles play a role? - Rodrigues, Magda Ferreira (2021)
Dissertação de Mestrado em Investigação Biomédica apresentada à Faculdade de Medicina